2023
DOI: 10.1055/a-2031-3859
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management and Clinical Course of Acute Pulmonary Embolism: The COPE Study

Abstract: Background. New diagnosis, risk stratification and treatment strategies became recently available for patients with acute pulmonary embolism (PE) leading to changes in clinical practice and potentially influencing short-term patients’ outcomes. Research question. The COntemporary management of PE (COPE) study is aimed at assessing the contemporary clinical management and outcomes in patients with acute symptomatic PE. Study design and Methods Prospective, non-interventional, multicentre study. The co-primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…These encompass critical aspects, including gender disparities, the impact of obesity, previous thrombotic events, and the influence of various medical conditions like cancer. These factors have been under investigation of the Italian COPE study's report, 37 potentially the most extensive and contemporary on pulmonary embolism (PE) with over 5,000 patients from more than 180 sites and which should serve as a valuable data source on current disease patterns, management strategies, and outcomes of acute PE.…”
Section: At Risk!mentioning
confidence: 99%
“…These encompass critical aspects, including gender disparities, the impact of obesity, previous thrombotic events, and the influence of various medical conditions like cancer. These factors have been under investigation of the Italian COPE study's report, 37 potentially the most extensive and contemporary on pulmonary embolism (PE) with over 5,000 patients from more than 180 sites and which should serve as a valuable data source on current disease patterns, management strategies, and outcomes of acute PE.…”
Section: At Risk!mentioning
confidence: 99%
“…29 30 In a recent prospective cohort study, only 1.2% of PE patients were directly discharged from the emergency department, while 5.8% were discharged early from the hospital, within 48 hours. 31…”
Section: Management Of Low-risk Patients and Early Discharge With The...mentioning
confidence: 99%
“…Recent registries have shown that about 60 to 70% of patients with acute PE qualify for intermediate risk of early death (in-hospital or after 30 days), defined as a hemodynamic stability associated an RV dysfunction and/or troponin alteration according to the guidelines of the European Society of Cardiology or the American Heart Association. 11 31 35 The expected mortality in these normotensive patients with clinical risk factors for death (PESI III–V or sPESI ≥ 1) and/or evidence of RV overload by imaging or by increased troponin varies between 2 and 15% in the short term. Among patients included in this wide risk category, there is a subgroup with a considerable risk of requiring rescue reperfusion or cardiopulmonary resuscitation for clinical deterioration.…”
Section: Doacs In the Treatment Of Pe Patients At Intermediate To Hig...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary embolism (PE) confined to the subsegmental pulmonary arteries, known as subsegmental PE, has increased in prevalence as detection capacities of computed tomography pulmonary arteriography (CTPA) have improved. Approximately 3% to 12% of PEs diagnosed using CTPA are subsegmental . The pharmacological treatment of patients with low-risk subsegmental PE is contested .…”
Section: Introductionmentioning
confidence: 99%